Estimation of dilatations for mappings more general than quasiregular mappings - Salimov, R. R.; Sevost'yanov, E. A. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We consider the so-called ring Q-mappings, which are natural generalizations of quasiregular mappings in a sense of Väisälä’s geometric definition of moduli. It is shown that, under the condition of nondegeneracy of these mappings, their inner dilatation is majorized by a function Q(x) to within a constant depending solely on the dimension of the space.